Lung cancer : principles and practice - Pass, Harvey I (Lippincott - Raven Publishers, 1996)
This comprehensive interdisciplinary text discusses the diagnosis and treatment of lung cancer. Combined modality treatments for small cell and non-small cell lung cancer are extensively described. Thorough coverage is also provided of the management of metastases and the complications of treatment. A section on biologic therapy is also included that describes the newer immunotherapeutic approaches to either palliation or cure.
Keywords: nádory plic; Lung Neoplasms; onkologie; pneumologie a ftizeologie